EDUCATIONAL SIGNIFICANCE OF TEACHING THE HISTORY OF TURKISH ART AND CULTURE TO STUDENTS - QOBILOVA E, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, by teaching Turkish folk culture and art, students can look at the music and art of the brotherly nations with respect, and through this, create a sense of creativity and internationalism.